ANTIMICROBIAL ACTIVITY AND CHEMICAL COMPOSITION OF TWO EXPERIMENTAL GELS BASED ON ESSENTIAL OILS - DASCALU (RUSU), Laura Monica; MOLDOVAN, Marioara; PRODAN, Doina; CIOTLAUS, Irina; CARPA, Rahela; ENE, Razvan; SAVA, Sorina; CHIFOR, Radu; BADEA, Mindra Eugenia (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In this study, the comparative testing of the antimicrobial efficacy of 2 experimental photosensitizers (PS-H; PS-T) based on natural compounds with a commercial one based on toluidine blue O (TBO) FotoSan® was performed, by antimicrobial tests with G- and G+ bacterial strains and through SEM microscopy on dental enamel, using LED phototherapy. For the formulation of the experimental natural photosensitizers we used Frankincense (T) and Thieves (H) essential oils (EO), used as photosensitizing agents in antimicrobial photodynamic therapy in the control of the microbial biofilm of the oral cavity. We also tested the composition of experimental photosensitizers by GC-MS chromatography. Our results suggest that EO should be further investigated as a promising source of natural compounds that can be used to combat bacterial strains. Essential oils can inhibit growth of a broad range of pathogens correlating to their presence in aromatic plants.